Correlation study on general and accelerated corrosion of the welded structure of aluminum alloy 2219 in N2O4. Issue 3 (5th May 2015) - Cathy Liu, Dr; Feng, Yuanbo; Huang, Zhiyong; Tian, Gan; Jin, Guofeng
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to present a correlation study on general and accelerated corrosion of the welded structure of aluminum alloy 2219 in N2O4. Design/methodology/approach – Corrosion experiments of the Tungsten Inert Gas (TIG)-welded aluminum alloy structure were conducted under both mild and accelerated corrosion conditions by changing the water content in N2O4. Findings – The experimental results indicated that both general and accelerated corrosion processes of the TIG-welded structure of aluminum alloy 2219 in N2O4 followed the linear equation ΔW = A + Bt, and the corrosion products were unchanged regardless of the water content in the N2O4 solution. Originality/value – The weight loss comparison method is used to identify the structure of the conventional aluminum welding and aluminum welding structure corrosion dinitrogen tetroxide in nitric acid accelerated corrosion relationship.